Rancang Bangun Sistem Informasi Manajemen Arsip Digital pada Koperasi “X” Kab. Bandung - Jawa Barat - Agus Nugraha (LPPM Universitas Koperasi Indonesia, 2025)
Archives are evidence or records of organisational activities, and every decision made by the cooperative management must be supported by data and information. The two characteristics of an archival system are reliability and accessibility which include aspects of the neatness, cleanliness, order, and security of the archive itself. Today, there are two types of archivemanagement systems: conventional and electronic (E-Archive). Both systems have similar management principles, but differ in how they are implemented virtually. E-Archive is separated into two categories: desktop-based (offline) and website-based (online). To construct the E-Archive, a system design is needed, which can be done using a variety of approach models, such asthe Waterfall Model, Activity Diagram, Use Case, and Class Diagram and interface Design. This system design can be developed and implemented into a web-based application.